Investigation of contact resistivity for Au–Ti–Pd–n-Si ohmic contacts for impatt diodes - Basanets, V. V.; Slepokurov, V. S.; Shinkarenko, V. V.; Kudrik, R. Ya.; Kudrik, Ya. Ya. (Technology and design in electronic equipment, 2015)
Both contact resistivity of Au–Ti–Pd–n-Si ohmic contact and mechanism of current flow are studied in the 100 – 360 K temperature range. A method is proposed for reduction of error in determination of contact resistivity based on analysis of statistical dependences of the measured contact resistivity values (which are in the range of (0.9 – 2.0).10–5 Ω.cm2). On the basis of the contact resistivity temperature dependence, it is found for an ohmic contact with barrier height of 0.22 eV that the field mechanism of current flow is predominant in the 100 – 200 K temperature range, while thermal-field emission with activation energy of 0.08 eV is predominant in the 200 – 360 K temperature range.